Reproductive Biology of Dalbergia sissoo Roxb - Vasudeva, S. P.; Sareen, T. S. (Indian Forester, 2011)
Dalbergia sissoo has flowering season of two months and the peak flowering period was for a week. The anthesis, dehiscence of anthers, stigma receptivity and pollinator activity showed synchronised diurnal rhythm. Flowers were pollinated by honey bees, beetles, butterflies and thrips. Despite the deep penetration of the self pollen tubes only 6% of selfed flowers produced fruits (against 44% in cross pollinated). This is due to the presence of self-incompatibility which is assessed to be of the gametophytic type. The low seed production helped in efficient dispersal of pods due to decreased wing loading of pods. It also helped in post dispersal establishment due to lack of competition between fewer genetically related seeds in a pod. Dispersal of seeds occurred through the agency of wind, birds and water. The abortion of flowers and immature fruits was common in Dalbergia sissoo. The fruit set in nature was 15% while the remaining 85 % flowers aborted. The fruit formation following deliberate selfing was 6 % in contrast to 44% from deliberate cross-pollination. Post zygotic factors have primarily been implicated to explain the abortion of fruits in D. sissoo. The average seed production was 1.30 formed from an average of 5 ovules. The mature brown pod was 1-3 seeded and rarely 4 seeded. Seed abortion was observed in 74% of cases with only 26% cases of the ovules developing into mature seeds. The distal most ovule developed into mature seed in 75% cases. Seed abortions were probably due to the dominant distal most ovule starving the other proximal ovules.